Mahārat al-kitābah bi-al-lughah al-ʿArabiyyah ladā ṭullāb al-ṣaff al-ʿāsyir fī al-madrasah al-thānawiyyah al-Islāmiyyah al-ḥukūmiyyah al-ūlā bi-Dilī Sardāng: dirāsah muqāranah bayna khirrījī al-madāris al-mutawassiṭah al-Islāmiyyah wa-al-madāris al-mutawassiṭah al-ʿāmmah - Budiman Siregar, Alim; Al Rasyid, Harun (UIR Press, 2026)
This study aims to analyze the differences in Arabic writing skills between students graduating from MTs and SMP in the tenth grade of MAN 1 Deli Serdang. This research is motivated by the differences in students’ initial abilities based on their previous educational backgrounds. The method used is a quantitative approach with a comparative design. Data analysis was conducted through normality testing, homogeneity testing, and the Independent Samples T-Test with the assistance of SPSS. The results of the study show that the average score of SMP graduates is 71.50, while that of MTs graduates is 81.57. The hypothesis test results indicate a significance value of < 0.05, which means that there is a significant difference between the two groups. Thus, it can be concluded that the writing skills of MTs graduates are better than those of SMP graduates. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted.